Evaluating “Take the Stairs, Wyoming!” Through the RE-AIM Framework: Challenges and Opportunities - Balis, Laura E.; Strayer, Thomas (Frontiers in Public Health, 2019)
Introduction: Health promotion delivery systems are increasingly being asked to implement policy, systems, and environmental interventions (PSEs). However, evaluating PSEs is challenging, especially in low-resource community settings. This paper describes the use of RE-AIM to evaluate a physical activity PSE delivered through University of Wyoming Extension and highlights challenges and opportunities in pragmatic, real-world program evaluation. Methods: Extension health educators adapted a point-of-decision prompt intervention encouraging stairway use through posters, called Take the Stairs, Wyoming! Reach was assessed through estimates of daily traffic, effectiveness was assessed through opportunistic interviews, adoption was calculated as the number and proportion of sites that agreed to hang posters, implementation was calculated as the proportion of sites with a poster in place at a two-week follow-up visit, and maintenance was assessed through six-month opportunistic interviews (individual level) and proportion of sites with a poster in place (organizational level). Results: Overall, the posters were widely adopted and most posters were implemented as intended. However, capturing reach, effectiveness, and maintenance was challenging, as health educators found the evaluation burdensome. Therefore, it was difficult to determine if the posters were effective at increasing physical activity levels. Discussion: Suggestions are provided for capturing reach, effectiveness, and maintenance data in community settings. Future efforts are needed to create evaluation tools to pragmatically measure effectiveness of PSEs on changing behaviors, as well as to prioritize program evaluation in Extension.